The image of a modern woman in the German supplements of magazine in Lodz in the interwar period - Kucner, Monika (Acta Universitatis Lodziensis. Folia Germanica, 2023)
Supplements to German newspapers in Lodz in the interwar period promoted an extremely modern type of woman, in line with the latest world trends. German magazines „Die Welt im Bilde. Sonntagsbeilage zur Neuen Lodzer Zeitung” and „Illustrierte Wochenblatt. Beilage zur Neuen Lodzer Zeitung” registered changes in lifestyle and propagated them among Lodz readers. The fashion promoted by Lodz accessories and lifestyle did not differ in any way from the latest European and world models. It was an expression of striving for modernity, for changing the way of thinking not only about women, but about the whole society. Introducing modern ideas into magazines resulted in the dissolution of old and obsolete forms.